Understanding the Practice, Application, and Limitations of Meta-Analysis. (January 2020) - Allen, Mike
This article discusses the basic assumptions and practices for meta-analysis as well as describing options and innovations for implementing this tool. Meta-analysis represents a family of techniques with different assumptions and procedures. I discuss some of the ongoing debates and limitations of the methods that continue to receive attention. In an era of "evidence-based" applications and educational material, meta-analysis (in all the forms) represents the best way to reduce Type II error and identify Type I error. Use of the technique provides facilitates the formulation and evaluation theoretical arguments as well as identifying the means to optimally generate future research efforts. The process of meta-analysis takes the scientist back to the future by reminding the community of the original premises that guided the formation of the statistical process.